2020
DOI: 10.1002/ccr3.3271
|View full text |Cite
|
Sign up to set email alerts
|

Is aripiprazole a key to unlock anorexia nervosa?: A case series

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…As a partial D2R agonist, aripiprazole would remediate low basal DA through its agonist properties while the reduced (partial) activation would mitigate super sensitized responses to phasic DA, putatively normalizing the dynamic range of dopamine signaling. Consistent with these ideas, aripiprazole has been shown to promote weight gain in AN (122,123). Interestingly, aripiprazole may have utility in stage 1 as well where its partial agonist properties may counteract escalating increases in dopamine.…”
Section: Discussionmentioning
confidence: 84%
“…As a partial D2R agonist, aripiprazole would remediate low basal DA through its agonist properties while the reduced (partial) activation would mitigate super sensitized responses to phasic DA, putatively normalizing the dynamic range of dopamine signaling. Consistent with these ideas, aripiprazole has been shown to promote weight gain in AN (122,123). Interestingly, aripiprazole may have utility in stage 1 as well where its partial agonist properties may counteract escalating increases in dopamine.…”
Section: Discussionmentioning
confidence: 84%
“…Tahilioglu et al reported a case series of eleven females with AN treated with aripiprazole. Improvements in obsessive eating attitudes and behaviors were found in all patients: the change in CGIS scores and BMI were statistically significant ( p < 0.001) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current review identified scant evidence for the use of aripiprazole in children and adolescents with AN. Two poor-quality studies [ 39 , 40 ] and one small case series with 4 patients [ 38 ] were included. Concerning the considered outcomes, all the studies reported an improvement in body-weight measures, while two studies showed improved psychopathology [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the combined D1 and D2 receptor blockage reduces fear and dread response, although it has limited effect on appetitive food response. While the evidence is still scant, there is now some emerging evidence that the partial D2 receptor agonist aripiprazole could be helpful in targeting illness related preoccupations and supporting insight in AN [ 101 , 102 , 103 , 104 , 105 ]. This may be consistent with animal studies that showed elevated survival of the ABA rodent model in response to stimulating dopamine neurons in the nucleus accumbens [ 106 ].…”
Section: Discussionmentioning
confidence: 99%